2022
DOI: 10.3389/fphys.2021.816624
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of IL-1β and TNF in the Spinal Cord Mediates Analgesia Produced by Ankle Joint Mobilization in Complete Freund Adjuvant-Induced Inflammation Mice Model

Abstract: ObjectiveThis study aims to investigate the effects of ankle joint mobilization (AJM) on mechanical hyperalgesia and peripheral and central inflammatory biomarkers after intraplantar (i.pl.) Complete Freund’s Adjuvant (CFA)-induced inflammation.MethodsMale Swiss mice were randomly assigned to 3 groups (n = 7): Saline/Sham, CFA/Sham, and CFA/AJM. Five AJM sessions were carried out at 6, 24, 48, 72, and 96 h after CFA injection. von Frey test was used to assess mechanical hyperalgesia. Tissues from paw skin, paw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…A recent study by Omura et al. demonstrated an escalation in M1 macrophage density after intraplantar injection of CFA, while M2 density remained unchanged at the site of inflammation ( 23 ). Our immunohistochemical staining experiments provided clear evidence that the knockout of Vamp3 in myeloid cells resulted in a substantial reduction in local macrophage accumulation in the plantar skin following CFA injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Omura et al. demonstrated an escalation in M1 macrophage density after intraplantar injection of CFA, while M2 density remained unchanged at the site of inflammation ( 23 ). Our immunohistochemical staining experiments provided clear evidence that the knockout of Vamp3 in myeloid cells resulted in a substantial reduction in local macrophage accumulation in the plantar skin following CFA injection.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of proinflammatory cytokines TNF-α and IL-6 in the CFA-injected paws were measured following previously described protocols ( 23 ), with minor modifications. Briefly, the injected paws (including skin and underlying muscle) at day 1 and day 14 post CFA administration were dissected and homogenized on ice in radioimmunoprecipitation assay (RIPA) lysis and extraction buffer (Thermo Fisher Scientific, Shanghai, China, catalog number 89900) containing a protease inhibitor cocktail set III (1:100 v/v; Merck, catalog number 539134) and 1 mM phenylmethylsulfonyl fluoride (Merck, catalog number P7626) before centrifugation at 13,000 rpm for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, analgesic effects with articular joint movement (AJM) treatment have been reported in a model of persistent inflammation. AJM did not altered cytokine levels at the inflammatory site, but centrally, AJM reduced the levels of pro-inflammatory cytokines IL-1β and TNF in the spinal cord, which suggests a central neuro-immunomodulatory effect ( 254 ). This data corroborates other pre-clinical studies showing that non-pharmacological interventions such as environmental enrichment (EE) can modulate the nociceptive and inflammatory responses in arthritis models.…”
Section: Treatments Targeting Macrophages and Glial Mechanisms In Per...mentioning
confidence: 94%
“…Among the approaches to desensitize central nervous system, healthcare professionals may use orthopedic manual therapy (OMT) techniques on patients with CMSKP, with the recommendation of its use in the clinical guidelines. 19 Although OMT mechanisms are not fully understood, a mechanical stimulus initiates a cascade of peripheral and central neurophysiological effects, 20 decreasing proinflammatory mediators, 21 decreasing mechanical hyperalgesia, 22,23 and activating supraspinal inhibitory pathways to produce a hypoalgesic and antinociceptive response. 24,25 Published systematic reviews (SRs) have demonstrated that OMT improves pain sensitivity and reduces central sensitization in patients with CMSKP, 5,26,27 although its effects are only limited to the immediate (after intervention) or short-term (from hours to days).…”
Section: What Is Newmentioning
confidence: 99%